BOARD DIVERSITY AND FINANCIAL LEVERAGE OF LISTED COMMERCIAL BANKS IN NIGERIA (2012 - 2022) (Journal of Global Accounting, 2024)
This study ascertained the effect of board diversity on financial leverage of listed deposit money banks in Nigeria for the period of eleven (11) years spanning from 2012 to 2022. Board size, and board independence were used to proxy board diversity while debt-to-equity ratio was used to measure financial leverage. In line with the objectives of the study, two hypotheses were formulated.  Ex-Post facto research design was employed. Thirteen (13) listed deposit banks constituted the sample size of this study. Secondary data were extracted from the annual reports and accounts of the sampled firms and were analysed using E-Views 10.0 statistical software. The study employed both descriptive and inferential statistical. The inferential statistics was applied using Pearson correlation and Panel Least Square (PLS) regression analysis. Findings from the empirical analysis showed that Board Size has a significant and positive effect on debt to equity ratio (β1 = 0.105965; P-value = 0.0030); Board Independence has a significant and positive effect on debt to equity ratio (β1 = 0.015668; P-value = 0.0000). Conclusively, board diversity has a significant and positive effect on financial leverage of listed deposit money banks in Nigeria at 5% level of significance. The study recommended that since gender-diverse boards influences the financial leverage of firms through better monitoring which is likely to increase confidence and encourage ownership by uninformed investors, hence, there is need for more female directors on the Board
Keywords: Board Diversity; Board Independence; Board Size; Debt-To-Equity Ratio; Financial Leverage